INCORPORATING THE RIGHT TO BE FORGOTTEN INTO UZBEKISTAN’S PERSONAL DATA LAW: PROSPECTS, CHALLENGES, AND COMPARATIVE INSIGHTS FROM GLOBAL PRIVACY FRAMEWORKS (International journal of artificial intelligence, 2026)
The rapid digitization of Uzbekistan’s socio-economic landscape, driven by the “Digital Uzbekistan 2030” strategy, necessitates a modernization of the national legal framework governing personal data. This article provides a comprehensive legal analysis of the feasibility and necessity of explicitly incorporating the “Right to Be Forgotten” (RTBF) into the Law of the Republic of Uzbekistan No. LRU-547 “On Personal Data” (LRU-547). While the current legislation outlines basic principles of data destruction, it lacks a mechanism for de-indexing information from search engines, leaving citizens vulnerable to the permanent stigmatization of obsolete digital footprints. Through a comparative analysis of the European Union’s General Data Protection Regulation (GDPR) and the landmark Google Spain jurisprudence, this study identifies critical gaps in Uzbek law. It examines the constitutional grounds for RTBF, explores the tension between privacy and freedom of information, and proposes specific legislative amendments to LRU-547, specifically creating a new Article 171. The article concludes that a codified RTBF, balanced by robust public interest safeguards, is essential for protecting the digital dignity of citizens and fostering international trust in Uzbekistan’s digital ecosystem.